Climate-smart agronomical practices for increasing agricultural production - Begam, A; Dutta, S; Das , K S; Mondal, S K (Indian Farming, 2022)
Climate-smart agronomic practices are being introduced to minimize abrupt changes in weather conditions like ambient temperature, rainfall pattern, wind velocity, relative humidity etc, which are prevailing in any country or state over a long-time span. These smart practices include several dimensions, viz. water smart, weather smart, nutrient smart, crop and cropping smart, energy smart, carbon smart and knowledge smart technologies. The impact of climate change or variability on agriculture livelihood could be minimized through various interventions under these smart dimensions. Several climate smart technologies related to agriculture have been successfully demonstrated by various ICAR Institutes and State Agricultural Universities which can be effectively implemented at farmers’ field within the particular locality. Moreover, climate smart agronomic practices not only increase the production and productivity of various agricultural commodities but, also improve the conservation of natural resources.